Solubility of 4-methyl-2-nitroaniline in fourteen organic solvents from T = (278.15 to 313.15) K and mixing properties of solutions. (July 2017) - Li, Xinbao; Wang, Mingju; Cong, Yang; Du, Cunbin; Zhao, Hongkun
Graphical abstract: Highlights: Solubilities of 4-methyl-2-nitroaniline in fourteen solvents were determined. Solubility data were correlated by using four thermodynamic models. Mixing properties of solutions were calculated. Abstract: The knowledge of solubility and solution thermodynamics for 4-methyl-2-nitroaniline in different solvents is essential for its preparation, purification and further theoretical studies. In this work, the solid-liquid equilibrium for 4-methyl-2-nitroaniline in fourteen organic solvents (methanol, ethanol, n -propanol, isopropanol, n -butanol, toluene, ethyl acetate, acetonitrile, 2-butanone, 1, 4-dioxane, N, N -dimethylformamide, carbon tetrachloride, 1, 2-dichloroethane and chlorobenzene) was built with the isothermal saturation method at temperatures T  = (278.15–318.15) K under pressure of 101.2 kPa, and the solubility values of 4-methyl-2-nitroaniline in these solvents were determined by a high-performance liquid chromatography (HPLC). Generally, the mole fraction solubilities obeyed the following order from high to low in different solvents: 2-butanone >  N, N -dimethylformamide > ethyl acetate > 1, 4-dioxane > (acetonitrile, 1, 2-dichloroethane) > chlorobenzene > (toluene, n -butanol) >  n -propanol > isopropanol > ethanol > methanol > carbon tetrachloride. The obtained solubility data of 4-methyl-2-nitroaniline in the selected solvents were correlated with the modified Apelblat equation, λh equation, Wilson model and NRTL model. Results showed that the largest values of relative average deviation and root-mean-square deviation acquired with the four models were no greater than 1.03% and 6.89 × 10 −4, respectively. The modified Apelblat equation provided better correlation results than the other three models. Moreover, the mixing properties, including mixing Gibbs energy, mixing enthalpy, mixing entropy, activity coefficient at infinitesimal concentration and reduced excess enthalpy were computed. The mixing process of 4-methyl-2-nitroaniline in the studied solvents was spontaneous and endothermic. The obtained solubility and thermodynamic studies would be very helpful for optimizing the preparation and purification process of 4-methyl-2-nitroaniline.